(3GdehLR aj eQGLY GdJQGLe hGdHdOGf hGdeUfaGJ hJYQjaGJ GdYdhe (B/s - (3GdWfGMj, eMehO eMeOs 1935-1999 ((3GdbGgQI (B- (3eUQ(B:s (3ecJHI GdNGfLi,s, 1985)
(3jJfGhd cJGH (B((3GdehLR aj eQGLY GdJQGLe hGdHdOGf hGdeUfaGJ hJYQjaGJ GdYdhe(B) (3hGdPj bGe HJCdjag O(B. (3eMehO eMeO GdWfGMj, ehVhY (B((3Odjd eQGLY(B) (3GdcJGH Odjd ehLR, Edi CHQR eQGLY JQGLe GdYdeGA, hGdCOHGA, hGdeUfajf aj cd af ef afhf GdJQGK GdYQHj, Ydi GNJdGa efGgL gPg GdeQGLY, eY PcQ TjA ef cJH GdVHW hGdJbjjO, hcJH GdHdOGf (B((3GdLZQGajG(B)(3, heQGLY GdcJH hGdeUfaGJ (B((3GdeQGLY GdHHdjhLQGajI(B)(3, GdJj JYjf Ydi QUO MQcI GdJCdja GdYQHj, heYQaI eSGQg YHQ GdbQhf hGdCReGf, hcJH JYQjaGJ GdYdhe heUWdMGJgG(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3HHdjhLQGajGs -- (3GdHdOGfs; (3HHdjhLQGajGs -- (3GdJQGLes; (3HHdjhLQGajGs -- (3GdeUfaGJs